The Realization of Interpersonal Negotiation in the Conversation - Hartati, Elysa (LPPM Universitas Mercu Buana Yogyakarta, 2015)
This study aimed toinvestigate how the students of English Department of theState University of Semarang realize interpersonal negotiation in their conversationand find out what kinds of problems that emerge when the students have aninterpersonal negotiation in their conversation.In analyzing the data, the descriptivequalitative approach was employed with small quantification was made to support theanalysis. Besides, the choices of mood, modality, speech roles as well as clause categorywere applied to analyze the data.The research findings showed that from theobservation towards 10 (ten) students done by practicing the conversation in pairs,there were only 3 (three) pairs that could realize the interpersonal negotiation in theirconversation. Most of students used declarative mood types (56.6%) more in theirconversation. It indicated that they wanted to initiate the exchanges by givinginformation more often. The modality that they used most was probabilitymodalization (41.2%). With high and medium categories of probability, the studentsexpressed their idea of the situation given.Though the students produced declarativemood more in their conversation, it did not directly indicate that they could realizeinterpersonal negotiation well. Most of the declaratives produced was moremaintaining the information exchange. The giving speech roles of the clauses producedby the students sometimes were inappropriate with the topic being discussed. It madethe conversation inconvenient. Even though the use of modalization and modulation toexpress interpersonal negotiation was not problematic, they did not use it optimally;only 17 clauses out of 143 clauses made use of them.Keywords : realization, interpersonal negotiation, conversation